Throwing accuracy of water polo players of different training age and fitness level in static position and after previous swimming - Platanou, T.; Botonis, P. (Biomechanics and Medicine in Swimming XI, 2010)
The aim of the present study was to compare throwing accuracy in a static position to after previous swimming in relation to training age and fitness level. Fifty (50) water polo players (aged: 11-17 yrs) were tested. Significant differences were observed in throwing accuracy between the static position and after previous swimming (F=58.05, P<0.001) by training age (F=21.8, P<0.001) and byfitness level (F=44.73, P<0.001). Moreover, throwing accuracy was greater in a static position than after previous swimming. Players with greater training age and better swimming performance had higher throwing accuracy than younger players and than those of with lower swimming performance. No significant differences were observed between Ä values in throwing accuracy in a static position or after previous swimming in relation to training age and fitness level.